Synthesis and Biological Evaluations of Betulinic Acid Derivatives With Inhibitory Activity on Hyaluronidase and Anti-Inflammatory Effects Against Hyaluronic Acid Fragment Induced Inflammation - Luo, Zhujun; He, Hao; Tang, Tiantian; Zhou, Jun; Li, Huifang; Seeram, Navindra P.; Li, Dongli; Zhang, Kun; Ma, Hang; Wu, Panpan (Frontiers in Chemistry, 2022)
We previously reported that the structural modifications of pentacyclic triterpenoids including oleanolic acid resulted in enhanced hyaluronidase inhibitory activity but whether this is applicable to other pentacyclic triterpenoids such as betulinic acid (BA) is unknown. Herein, we synthesized BA derivatives with an α,β-unsaturated ketene moiety and evaluated for their: 1) hyaluronidase inhibitory activity and, 2) anti-inflammatory effects against lipopolysaccharides (LPS) induced inflammation. Compared to BA, the BA derivatives exerted improved anti-hyaluronidase activity (26.3-72.8% vs 22.6%) and anti-inflammatory effects by reducing nitrite production in BV2 cells (3.9-46.8% vs 3.4 %) and RAW264.7 cells (22.7-49.2 % vs 20.4%). BA derivatives inhibited LPS-induced production of pro-inflammatory cytokines in THP-1 cells (15.2-22.4%). BA derivatives also exerted promising anti-inflammatory effects against hyaluronic acid fragment induced nitrite production (8.6-35.6%) in BV2 cells. BA derivatives showed augmented anti-hyaluronidase and anti-inflammatory effects but further biological evaluations using in vivo models are warranted to confirm their efficacy.